Two cases reports: Severe liver injury caused by 1,2,3-trichloropropane poisoning - Li, Chen; Hu, Jinhua; Su, Haibin (Frontiers in Public Health, 2023)
Background: 1,2,3-trichloropropane (TCP) poisoning can induce liver damage in humans and animals, but reports of severe liver injury and its histology are rare. We presented two cases of 1,2,3-TCP inhalation poisoning resulting in severe liver injury confirmed by exposure history, toxicology, biochemical index and pathology. Case description: Two young male presented acute poisoning process with mild to moderate early symptoms, and developed severe jaundice and coagulation dysfunction after exposure to 1,2,3-TCP. The total bilirubin (TBIL) in case 1 and case 2 reached the peak value of 635.8 μmol/L and 437.1 μmol/L on the 25th and 22nd days respectively. Their liver enzymes and international normalized ratio increased rapidly to peak and fell back, and TBIL remained at a high level. 1,2,3-TCP was detected in their blood, and their liver histology indicated severe necrosis of hepatocytes, infiltration of massive inflammatory cells, and cholestasis. They all finally recovered after a long time of treatment. Conclusions: The two cases in this study demonstrate that 1,2,3-TCP inhalation poisoning without any protective measures can induce severe liver injury in humans.